Effects of photobiomodulation (660 nm laser) on anthracycline extravasation: An experimental study - Freitas, Karina Alexandra Batista da Silva [UNESP]; Minicucci, Eliana Maria [UNESP]; da Silva, Valéria Flávia Batista; Menozzi, Benedito Donizete [UNESP]; Langoni, Hélio [UNESP]; Popim, Regina Célia [UNESP] (FapUNIFESP (SciELO), 2022)
Objective: to investigate the effect of using different agents (topical hyaluronidase, photobiomodulation, and the association of photobiomodulation with topical hyaluronidase) in preventing the formation of lesions caused by doxorubicin extravasation, as well as in the reduction of lesions formed by extravasation of this drug. Method: a quasi-experimental study conducted with 60 Wistar rats, randomized into four groups with 15 animals each. Group 1 (Control); Group 2 (Hyaluronidase); Group 3 (Photobiomodulation); and Group 4 (Hyaluronidase + Photobiomodulation). A wound was induced by applying 1 mg of doxorubicin to the subcutaneous tissue of the back of the animals. The concentration of topical hyaluronidase was 65 turbidity units/g and the energy employed was 1 joule of 100 mW red laser per square centimeter. With macroscopic evaluation every two days for 28 days, the following variables were observed: skin integrity, presence of blisters, hyperemia, exudate, bleeding, edema, crust, peeling and granulation tissue. Results: the animals from the groups subjected to photobiomodulation obtained better results in the assessment of the following variables: bleeding, hyperemia, exudate, intact skin and edema. Conclusion: it was evidenced that the association of photobiomodulation with topical hyaluronidase was effective in reducing the local effects and assisted in the wound healing process, and that PBM alone was able to prevent appearance of lesions.
Efectividad de la auriculoterapia para la ansiedad, el estrés o el burnout en profesionales de la salud: metaanálisis en red
Efetividade da auriculoterapia para ansiedade, estresse ou burnout em profissionais da saúde: metanálise em rede
Keywords: Adverse Effects; Antineoplastic Agents; Extravasation of Diagnostic and Therapeutic Materials; Low-Level Light Therapy; Nursing Care; Wistar Rats